Transhumanismo, posthumanismo, Antropoceno: notas sobre la humanidad vertiginosa. - Arias Maldonado, Manuel (Pasajes: Revista de Pensamiento Contemporáneo, 2019)
The article presents the discussion on possessing the supreme degree of intelligence promised by transhumanists. Topics include Nietzsche's perspective challenges us to reconsider our moral frameworks and recognize the limitations of our current understanding when contemplating future advancements; and nuanced and adaptable understanding of morality in the face of technological advancement.